THE EFFECT OF GOOD CORPORATE GOVERNANCE AND COMPANY CHARACTERISTIC ON ENVIROMENTAL DISCLOSURE - Moh Syuad Iman; Novi Darmayanti; Martha Suhardiyah (Journal of Economics, Business, and Government Challenges, 2021)
This study aims to examine the effect of good corporate governance and company characteristics on environmental disclosure. Good corporate governance is represented by the variable size of the board of commissioners, independent commissioners, and the audit committee. Meanwhile, company characteristics are represented by size and age variables. This research is a quantitative research. The data taken is secondary data. The data in this study were obtained using library research. The population in this study are companies listed on the BURSA EFEK INDONESIA (BEI) in the period 2015 - 2020. The research sample taken is companies that are included in the natural resources sector and collected using purposive sampling method. A total of 6 companies were determined as the research sample. The data analysis method in this study uses a statistical scientific approach. The analytical method used is multiple regression analysis consisting of classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test) and hypothesis testing (coefficient of determination, t test, F test). The results of this study indicate that the adjusted R2 value is 98.9% which means that the environmental disclosure variable can be explained by the five independent variables, namely the board of commissioners (DK), independent commissioners (KOMIN), audit committee (KOAU), size (SIZE), and age (AGE). The results of the t-test of this study indicate that: the board of commissioners, independent commissioners, audit committees, size, age have a positive effect on environmental disclosure. While the results of the F test from this study prove that the board of commissioners, independent commissioners, audit committee, size, age have a simultaneous effect on environmental disclosure.